اختيارات وترجيحات الإمام المارغني في النّجوم الطّوالع - جمعا ودراسة- - بالقط, عبد الجبار (University of Eloued جامعة الوادي, 2017)
هذا البحث عبارة عن جمع تسعين اختيارًا للإمام المارغني التي ضمّنها كتابه الماتع الموسوم بـ "النّجوم الطّوالع على الدّرر اللّوامع في أصل مقرإ الإمام نافع" ودراستها، إبتدأتُه بمقدّمة عرضتُ فيها أهمّيّة البحث وأسباب اختياره، وأهدافه والخطّة المتّبعة وغيرها من النّقاط التي لابدّ منها، وقسّمت البحث إلى فصلين، وجعلت بين يديهما تمهيدًا، فرّقت فيه بين معنى الاختيار والتّرجيح وبيّنتُ مفهومه عند القرّاء خلافًا لغيرهم من الفقهاء وغيرهم، فجعلته كالمفتاح لدراسة الاختيارات، ثم طرقت الفصلين، وكلاًّ منهما حوى مباحث، تطرّقت في الفصل الأوّل منهما، إلى التعريف بالعلاّمتين؛ تعريفًا موجزًا لابن برّي صاحب نظم الدّرر، وتعريفًا لشارحه المارغني، وشرحه "النّجوم الطّوالع"، وفي الفصل الثّاني، وهو صُلبُ الموضوع، أوردت فيه مبحثين، عرضتُ في الأوّل منهما منهج المارغني في اختياراته والقواعد التي مشى عليها، مع ذكر أهمّ عباراته في ذلك من خلال كتابه "النّجوم الطّوالع"، وثنّيتُه بمبحث عرضتُ فيه اختياراته المستمدّة من كتابه المذكور مع دراستها والتّعليق عليها، لأختم هذا البحث بخاتمة حوت نتائج وتوصيّات أرى من المهمّ ذكرها والتّنبيه عليها عسى أن تكون للبحث ثمرة نافعة، وخلاصة مفيدة This research is a collection of the ninety choices of the Imam Al-Marighni, which have been included in his interesting book which entitled for "Annojum Attawalaa Ala Addorar Allawamaa fi Asl Maqra'i Al'Iimam Nafie" and their study. I have begun it with an introduction which I have presented the importance of the research, the reasons for its selection, its objectives, the followed plan and other necessary points. I have divided the research into two chapters and an introductory chapter which I have differentiated in it between the meaning of choice and preference and I have showed its concept from the reciters unlike other scholars , and I have made it the key to study the choices, and then I have dealt the two chapters, each one contains sections. I have touched on the first chapter, the definition of the two scholars, Ibn Birri’s Nathm Eddorar book and its explainer Al-Marighni and his explanation that is "Annojum Attawalaa". In the second chapter which is the crux of the subject, I have mentioned two sections, in the first one I have showed Al-Marighni’ approach in his choices and the rules which have been applied and I have mentioned the most important expressions through his book which is "Annojum Attawalaa". In the second section, I have showed his choices that have been derived from his mentioned book with their study and comment. I have concluded this research with a conclusion which has contained results and recommendations, I think it is important to mention and urge them that may be useful for the research and a beneficial summary
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: الاختيارات والترجيحات، القراءات، الأوجه القرائية، الإمامان ابن برّي والمارغني; Choices in the kiraate, faces of the kiraate, the Imam ibn Berri, and the Imam Al-Marighni